-2x2 + 9x - 12 = 0Then apply the quadratic formula.
Yes
2x2 + 3x - 20 = (x + 4)(2x - 5).
It is, as stated, 2x2 + x - 1 = 0. That is the quadratic form.
Using the quadratic equation formula: x = 1 or x = -10
-2x2 + 9x - 12 = 0Then apply the quadratic formula.
Yes
2x2 + 3x - 20 = (x + 4)(2x - 5).
It is, as stated, 2x2 + x - 1 = 0. That is the quadratic form.
Using the quadratic equation formula: x = 1 or x = -10
None because the discriminant of this quadratic equation is less than zero.
quadratic
By using the quadratic equation formula: x = -5 and x = 3
2x2-10+7 = 0 Solving the quadratic equation using the quadratic formula will give you two solutions and they are: x = (5 - the square root of 11)/2 or x = (5 + the square root of 11)/2
There are no powers e.g 2x2 would be due to the 2
A Quadratic statement
It can't be solved because its discriminant is less than zero